Spiritual Education (A Religious, Spiritual, Sufi, Psychological and Pedagogical Evaluation that Opens Ways to Spiritual Strengthening) - Yılmaz, Fatmanur (Fırat University, 2024)
Nowadays, the increasingly increasing focus on material things and the decreasing importance given to spirituality have started to have negative effects on people. As these observed negativities began to increase, the importance of spirituality was recognized by positive sciences such as psychology, medicine and pedagogy and began to be addressed scientifically again. Studies on this subject are increasing. In this study, the book titled "Spirituality Education", written about spirituality, will be evaluated in terms of its content, scope, contributions to the field and suggestions it offers. Assoc. Dr. This work, written by Yasin Yiğit, is 253 pages and consists of 4 chapters. It is noteworthy that an original spiritual education model is presented, especially in the last chapter of the book. It can be said that the book makes a significant contribution to the systematization of spirituality education. Reading the book by all stakeholders in the field of theology will contribute to their professional development, and the study can be read by everyone in terms of personal development.

Günümüzde hızlanarak artan maddiyata yöneliş ve maneviyata verilen önemin azalması insanda olumsuz tesirler oluşturmaya başlamıştır. Bu gözlenen olumsuzlukların artmaya başlamasıyla maneviyatın önemi psikoloji, tıp, pedagoji gibi pozitif bilimler tarafından fark edilip tekrar bilimsel olarak ele alınmaya başlanmıştır. Bu konuda yapılan çalışmalar giderek artmaktadır. Bu çalışmada ise maneviyatla ilgili olarak yazılmış “Maneviyat Eğitimi” adlı kitap içerik, kapsam, alana sağladığı katkılar, sunduğu öneriler bakımından değerlendirilecektir. Doç. Dr. Yasin Yiğit tarafından kaleme alınan bu eser 253 sayfa olup 4 bölümden oluşmaktadır. Özellikle kitabın son bölümünde yer alan özgün bir maneviyat eğitimi modeli ortaya koyulmuş olması dikkat çekicidir. Kitabın maneviyat eğitiminin sistematik hale gelmesine önemli bir katkı sunduğu söylenebilir. Kitabın ilahiyat alanındaki tüm paydaşlar tarafından okunması mesleki gelişimlerine katkı sağlayacaktır, ayrıca çalışma, kişisel gelişim açısından herkes tarafından okunabilir.
Maneviyat Eğitimi (Manen Güçlenmenin Yollarını Aralayan Dinî, Manevi, Tasavvufi, Psikolojik ve Pedagojik Bir Değerlendirme)
Keywords: Religious Education; Din Eğitimi